Bridging Research and Extension Gaps of Rice Yield in Kurnool District of Andhra Pradesh - E.S. V. Narayana Rao,; K.Nirmal Ravi Kumar,; Waheeda Munawer, (Journal of Agricultural Extension Management, 2025)
Rice is the staple food for the Indian population and plays an important role in the national economy of the country. However, the yield level of rice at the farmers' level and in Front Lin~ Demonstrations is not on par with potential yield. There are research and extension gaps which need to be bridged to increase rice production and productivity, to improve the efficiency of land and labor use, reduce production costs and increase food security. The objectives of this study were to assess the research and extension gaps in · cultivating rice through need based technological interventions, and to prioritize these interventions. A total of five technological interventions were purposively selected to ascertain research and extension gaps. The -results reveal that both research and extension • gaps are still prevalent with reference to the selected technological interventions. It’s high time that farmers adopt the interventions on a scientific scale to minimize the gap to the extent possible